First description of the soft part anatomy of Ilyocypris ramirezi Cusminsky & Whatley (Crustacea, Ostracoda) from Argentina, South America - D´ambrosio, D. Sabina; Díaz, Analía R. (Zootaxa, 2015)
The anatomy of the soft parts of Ilyocypris ramirezi Cusminsky & Whatley, 1996 is described and illustrated for the first time, based on findings of this species from water bodies in the shallow areas of the Llancanelo basin, south-west of Mendoza Province, Argentina. This species is common in Quaternary and extant environments of the Pampa and Patagonian regions. Its distribution is now extending in Argentina to the Central-West area, locally named “Cuyo region”. Ilyocypris ramirezi is a good environmental indicator and constitutes a useful tool in paleolimnological studies.